PEMBERIAN BEBERAPA KONSENTRASI EKSTRAK BIJI MAHKOTA DEWA (Phaleria macrocarpa L.) TERHADAPMORTALITAS HAMA PENGGEREK TONGKOL JAGUNG (Helicoverpa armigera Hubner) DI LABORATORIUM - Ihsanul Fikri; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Helicoverpa armigera Hubner is a pest on the corn plant. H. armigera pest control is usually performed using synthetic insecticides, however the unwise of them use can cause negative impacts to humans and the agricultural environment, then necessitating alternative insecticides that are safer and environmentally friendly such as the use of the seed extract of the crown of god (Phaleria macrocarpa L). The purpose of this study was to obtain a concentration of the extract of the crown of god seeds which was effective in controllingH. armigera. The research was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, Riau University, Pekanbaru from September to November 2020. Experiments were carried using a completely randomized design (CRD) with 5 treatments and 4 replications so that obtained 20 experimental units. Concentration of the seed extract of the crown of god as treatment are 0 g.l-1 water, 25 g.l-1 water, 50 g.l-1 water, 75 g.l-1 water and 100 g.l-1 water. The result showed that the concentration of the extract of the crown of god seeds 75 g.l-1 water able to control pests H. armigera and can cause a total mortality of 82,50% with an initial death time of 8,50 hours and lethal time 50 of 17,75 hours. Keywords: Helicoverpa armigeraHubner.,crown of god, corn, mortality.